Preparation process of surface gate dielectric layer of low-dimensional material field effect transistor

By first using hydrogen peroxide to form a primary gate dielectric layer on the surface of low-dimensional materials, and then using ozone to grow a gate dielectric layer of target thickness at high temperatures, the problems of insufficient reaction between oxygen sources and metal sources and excessive oxidation in the prior art are solved. , realizes high-quality and dense gate dielectric layer preparation, meeting the performance requirements of field effect transistors.

CN119230414AInactive Publication Date: 2024-12-31SUZHOU ENJING SEMICON TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411767197.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the atomic layer deposition process with water as the oxygen source or ozone as the oxygen source is prepared on the surface of low-dimensional materials, the requirements of field effect transistors for high-quality gate dielectric layers cannot be met, and the oxygen source and metal source are the requirements of the oxygen source and the metal source. Inadequate reactions or strong oxidation properties lead to defects, vacancy and structural damage.

Method used

Using hydrogen peroxide as the oxygen source to form a primary gate dielectric layer under low temperature conditions, and then using ozone as the oxygen source to continue to grow a gate dielectric layer of target thickness under high temperature conditions. The oxidation of hydrogen peroxide is moderate and the high oxidation of ozone is combined to form a dense And a uniform gate dielectric layer.

Benefits of technology

It effectively reduces the oxygen vacancy in the gate dielectric layer, improves its mass and density, meets the requirements of field effect transistors for high-quality gate dielectric layers, and avoids structural damage caused by insufficient reaction between oxygen sources and metal sources and high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230414A_ABST
    Figure CN119230414A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electronic components, in particular to a preparation process of a low-dimensional material field effect transistor surface gate dielectric layer, which comprises the following steps: S1, placing a substrate in a cavity of an ALD reaction device, S2, introducing a hydrogen peroxide precursor into the cavity for surface adsorption, and then purifying the cavity; s3, the temperature in the cavity is increased to 50-200 DEG C from the room temperature, metal source steam formed in the metal source bottle is brought into the cavity by high-purity nitrogen through a pipeline and reacts with the hydrogen peroxide precursor adsorbed on the surface of the low-dimensional material, and then the cavity is purified; s4, repeating the steps S2 and S3 for multiple times, and forming a primary gate dielectric layer on the surface of the low-dimensional material; switching an oxygen source from a hydrogen peroxide source to an ozone source, and continuing to grow a gate dielectric layer under a high-temperature condition. According to the preparation process, the structure of the material cannot be damaged, the primary dielectric layer can have good compactness, and meanwhile all the advantages of preparing the gate dielectric layer under the high-temperature and high-oxidation conditions are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electronic components, and in particular to a preparation process of a surface gate dielectric layer of a low-dimensional material field effect transistor. Background Art

[0002] An integrated circuit is a microelectronic device or component; the gate dielectric layer is an important component of the integrated circuit and is located between the gate and the channel; the main function of the gate dielectric layer in the integrated circuit is to control the flow of current in the channel, thereby realizing the switching control of the transistor.

[0003] With the rise of emerging technologies such as 5G, AI, and the Internet of Things, the integrated circuit industry has also ushered in new development opportunities. The manufacturing process technology of integrated circuits has also continued to develop, and the market size has continued to expand. In order to improve the integration of integrated circuits, increase the operating speed of devices and reduce power consumption, the characteristic dimensions of integrated circuit devices are constantly shrinking; the thickness of the gate dielectric layer is also constantly decreasing with the miniaturization of the characteristic dimensions, in order to achieve the purpose of improving the gate electrode capacitance and the gate's control over the channel. However, the continuous decrease in the thickness of the gate dielectric layer will cause the gate leakage current to increase sharply, thereby reducing the reliability of integrated circuit devices. In order to solve the above problems, high-k materials are introduced as new gate dielectric layer materials, such as hafnium oxide (HfO 2 ‌), ‌Zirconium Oxide (ZrO 2 ), barium strontium titanate (BST), etc. These high-k materials are materials with high dielectric constants, which can not only reduce leakage current, but also improve the control ability of the gate over the channel, thereby further improving the performance and reliability of the integrated circuit; and the high-k gate dielectric layer is usually prepared by atomic layer deposition (ALD).

[0004] Common one- and two-dimensional materials, such as carbon nanotubes, graphene, molybdenum disulfide (MoS 2 ), tungsten disulfide (WS 2 ), molybdenum diselenide (MoSe 2 ), tungsten diselenide (WSe 2), MXene materials, etc., all have the characteristics of extreme channel thickness and high mobility, which can significantly increase the gate control ability and are new electronic materials that are expected to continue to extend Moore's Law. However, there are no dangling bonds on the surface of these materials. When the gate dielectric layer is prepared on the surface of these materials using the traditional atomic layer deposition process (ALD) with water as the oxygen source or ozone as the oxygen source, the interface state of the prepared gate dielectric layer is much higher than that of silicon-based CMOS transistors, and cannot meet the requirements of field effect transistors for high-quality gate dielectric layers; and when the gate dielectric layer is prepared using the ALD process using water as the oxygen source, due to the insufficient oxidizing property of the water source, a large number of defects and vacancies in the gate dielectric layer will occur during the preparation process due to the insufficient reaction between the oxygen source and the metal source, resulting in poor performance of the circuit device, or even the phenomenon of failure to work; when the gate dielectric layer is prepared using the ALD process using ozone as the oxygen source, due to the strong oxidizing property of ozone, it is easy to oxidize and decompose with one- and two-dimensional materials, causing the surface of the one- and two-dimensional materials to be corroded or undergo different degrees of crystal transformation, thereby destroying the one- and two-dimensional material structure and affecting carrier transport to a certain extent. Therefore, developing a high-quality, ultra-thin gate dielectric layer preparation process for low-dimensional materials that is compatible with large-area processes is the key to the widespread application of low-dimensional electronic devices.

[0005] The present invention provides a process for preparing a gate dielectric layer on the surface of a field effect transistor of a low-dimensional material, so as to solve the problems existing in the prior art that the gate dielectric layer prepared by the atomic layer deposition process using water as an oxygen source or ozone as an oxygen source cannot meet the requirements of the field effect transistor for a high-quality gate dielectric layer, the reaction between the oxygen source and the metal source is insufficient resulting in a large number of defects and vacancies in the gate dielectric layer, the oxidizing property of the oxygen source is too strong or the high temperature environment causes the surface structure of the one- or two-dimensional material to be destroyed, and the like. Summary of the invention

[0006] The purpose of the present invention is to provide a process for preparing a gate dielectric layer on the surface of a field effect transistor made of a low-dimensional material, so as to solve the problems existing in the prior art that the gate dielectric layer prepared by the atomic layer deposition process using water as an oxygen source or ozone as an oxygen source cannot meet the requirements of the field effect transistor for a high-quality gate dielectric layer, the reaction between the oxygen source and the metal source is insufficient, resulting in a large number of defects and vacancies in the gate dielectric layer, and the surface structure of the low-dimensional material is destroyed due to the excessive oxidizing property of the oxygen source or the high temperature environment.

[0007] The technical solution of the present invention is: a process for preparing a surface gate dielectric layer of a low-dimensional material field effect transistor, comprising the following steps: S1, placing a substrate having a low-dimensional material in the chamber of the ALD reaction device, and adjusting the pressure inside the chamber to 5-50Pa; S2, introducing a hydrogen peroxide precursor into the chamber for surface adsorption, so that the hydrogen peroxide precursor is adsorbed on the surface of the low-dimensional material, and then introducing high-purity nitrogen into the chamber to purify the chamber; S3, raising the temperature in the chamber from room temperature to 50-200°C, and at the same time raising the temperature in the metal source bottle to the rated temperature, so that metal source vapor is formed in the metal source bottle, and is brought into the chamber through a pipeline by high-purity nitrogen gas, so that the metal source precursor reacts with the hydrogen peroxide precursor adsorbed on the surface of the low-dimensional material to form a single layer of the primary gate dielectric layer, and then, high-purity nitrogen gas is introduced into the chamber to purify the chamber, completing a growth cycle; S4, repeating steps S2 and S3 multiple times to form a primary gate dielectric layer of target thickness on the surface of the low-dimensional material; S5, introducing an ozone precursor into the chamber to allow the ozone precursor to be adsorbed on the primary gate dielectric layer on the surface of the low-dimensional material, and then introducing high-purity nitrogen into the chamber to purify the chamber; S6, raising the temperature in the chamber to 230-320°C, and at the same time raising the temperature in the metal source bottle to the rated temperature, so that metal source vapor is formed in the metal source bottle, and is brought into the chamber through a pipeline by high-purity nitrogen gas, so that the metal source precursor reacts with the ozone precursor adsorbed on the primary gate dielectric layer, and then high-purity nitrogen gas is introduced into the chamber to purify the chamber, completing a growth cycle; S7. Repeat steps S5 and S6 multiple times to form a gate dielectric layer of target thickness on the surface of the low-dimensional material.

[0008] Preferably, in step S2, the carrier gas volume of the hydrogen peroxide precursor is 18-25 sccm, and the pulse duration of the hydrogen peroxide precursor is 20-500 ms.

[0009] Preferably, in step S3, the rated temperature is 20-200°C; The carrier gas volume of the metal source precursor is 20 sccm, and the pulse duration of the metal source precursor is 20-500 ms.

[0010] Preferably, in step S3, the metal source precursor is any one of trimethylaluminum, tetrakis(dimethylamino)hafnium, tetrakis(ethylmethylamino)hafnium, and tris(methylcyclopentadienyl)yttrium.

[0011] Preferably, the growth cycle of the primary gate dielectric layer is 10-200 cycles; and the target thickness of the primary gate dielectric layer is 1.5-2.5 nm.

[0012] Preferably, the chamber is purified for 10-30 seconds.

[0013] Preferably, the target thickness of the gate dielectric layer is 5-12 nm.

[0014] Compared with the prior art, the advantages of the present invention are: (1) The present invention provides a process for preparing a gate dielectric layer on the surface of a low-dimensional material field effect transistor. The process comprises the following steps: first, under low temperature conditions, using hydrogen peroxide as an oxygen source to prepare a primary dielectric layer on the surface of the low-dimensional material field effect transistor; then, using ozone as an oxygen source, continuing to grow a gate dielectric layer of a target thickness under high temperature conditions; because hydrogen peroxide is easily physically adsorbed on the surface of the material under low temperature conditions to form a primary seed layer, it can make up for the defect that there are no dangling bonds on the surface of the low-dimensional material; and because hydrogen peroxide has moderate oxidizing properties, it will not destroy the structure of the material itself due to excessive oxidizing properties, and can also fully react with a metal source to effectively reduce oxygen vacancies in the gate dielectric layer, so that the primary dielectric layer has excellent The method can improve the compactness and uniformity of the gate dielectric layer, and effectively reduce the surface state density of the gate dielectric layer, thereby improving the quality of the gate dielectric layer; in addition, the prepared primary dielectric layer can be used as a protective layer, so that the structure of the low-dimensional material will not be destroyed by the ozone and high-temperature environment with strong oxidizing property, thereby making the preparation process have all the advantages of the gate dielectric layer prepared under high-temperature and high-oxidizing conditions; it solves the problems existing in the prior art that the gate dielectric layer prepared by the atomic layer deposition process using water as the oxygen source or ozone as the oxygen source cannot meet the requirements of the field effect transistor for the high-quality gate dielectric layer, the reaction between the oxygen source and the metal source is insufficient, resulting in a large number of defects and vacancies in the gate dielectric layer, and the surface structure of the low-dimensional material is destroyed due to the excessive oxidizing property of the oxygen source or the high-temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] The present invention will be further described below in conjunction with the accompanying drawings and embodiments: Figure 1 This is a TEM image of a gate dielectric layer prepared using hydrogen peroxide-ozone as an oxygen source according to Example 1 of the present invention; Figure 2 The performance test results of the FET device described in Example 1 of the present invention; Figure 3 This is a TEM image of the gate dielectric layer prepared using water as the oxygen source in Comparative Example 1 of the present invention; Figure 4 The performance test results of the FET device described in Comparative Example 1 of the present invention; DETAILED DESCRIPTION

[0016] The present invention is further described in detail below in conjunction with specific embodiments: It should be further explained that the "low-dimensional materials" recorded in the present invention refer to "one- and two-dimensional materials".

[0017] A process for preparing a gate dielectric layer on the surface of a low-dimensional material field effect transistor comprises the following steps: S1. Place the substrate with low-dimensional materials in the chamber of the ALD reaction device, and adjust the pressure inside the chamber to 5-50Pa. In the present invention, the ALD reaction device used is a dual-chamber structure, and the inner chamber is arranged inside the outer chamber; the outer chamber mainly plays the role of heat preservation and pressure preservation, which is used to ensure that the temperature and pressure inside the inner chamber can reach the temperature and pressure values ​​required for preparing the gate dielectric layer, and keep the pressure and temperature inside the inner chamber in a stable state during the preparation of the gate dielectric layer, and the inner chamber is used to hold the substrate with low-dimensional materials, and the oxygen source, metal source and other gases are also introduced into the inner chamber, and deposition, reaction, etc. are carried out in the inner chamber to prepare the gate dielectric layer; the pressure inside the inner chamber and the pressure inside the outer chamber should be within the range of 5-50Pa. In the present invention, the "chamber" recorded refers to the inner chamber, the "inside the chamber" recorded refers to the inside of the inner chamber, and the "outside the chamber" recorded refers to the inside of the outer chamber.

[0018] S2, introduce hydrogen peroxide precursor (H 2 O 2 ), surface physical adsorption is performed to make the hydrogen peroxide precursor adsorbed on the surface of the low-dimensional material to form a primary seed layer, and then high-purity nitrogen is introduced into the chamber to purify the chamber. In the process of introducing the hydrogen peroxide precursor into the chamber, the carrier gas volume of the hydrogen peroxide precursor is 15-25sccm; the pulse duration of the hydrogen peroxide precursor is 20-500ms, so that the hydrogen peroxide precursor is uniformly adsorbed on the surface of the low-dimensional material. Since the hydrogen peroxide precursor introduced into the chamber is excessive, after the hydrogen peroxide precursor is uniformly adsorbed on the surface of the low-dimensional material, a part of the unadsorbed hydrogen peroxide precursor will remain in the chamber; in order to ensure that each round of deposition only adds one layer of atoms or molecules, high-purity nitrogen needs to be introduced for a certain period of time to clean and purify the chamber and blow away the excess hydrogen peroxide precursor; at the same time, in order to avoid blowing off part of the hydrogen peroxide precursor adsorbed on the surface of the low-dimensional material, the purification time should not be too long. In the invention, the purification time is controlled within the range of 10-30s.

[0019] S3. Raise the temperature in the chamber from room temperature to 50-200°C, and raise the temperature in the metal source bottle to the rated temperature, so that metal source vapor, i.e., metal source precursor, is formed in the metal source bottle, and is brought into the chamber by high-purity nitrogen through a pipeline, and reacts with the hydrogen peroxide precursor adsorbed on the surface of the low-dimensional material to form a single layer of the primary gate dielectric layer. After that, high-purity nitrogen is introduced into the chamber to purify the chamber to complete a growth cycle. Among them, in order to ensure or increase the reaction rate of the metal source precursor and the hydrogen peroxide precursor, the temperature in the chamber should not be lower than the reaction temperature of the metal source precursor and the hydrogen peroxide precursor, and the temperature in the chamber can be set according to the different metal source precursors used; however, since low-dimensional materials are easily oxidized, decomposed, or undergo different degrees of crystal transformation under high temperature and strong oxidizing environment, the structure of the low-dimensional material will be destroyed and its carrier transmission effect will be affected to a certain extent; therefore, the temperature in the chamber should not exceed 200°C. Raising the temperature in the metal source bottle to the rated temperature helps to convert the metal source precursor in the metal source bottle from solid and liquid to gas, that is, metal source vapor, and is brought into the chamber through a pipeline by high-purity nitrogen, so that the metal source precursor reacts with the hydrogen peroxide precursor adsorbed on the surface of the low-dimensional material to obtain a single layer of the primary gate dielectric layer; wherein the rated temperature can also be set according to the physical and chemical properties of the metal source precursor used. In the process of introducing the metal source precursor into the chamber, the carrier gas volume of the metal source precursor is 18-25sccm, and the pulse time is 20-500ms. After the reaction between the metal source precursor and the hydrogen peroxide precursor is completed, a growth cycle is completed; and high-purity nitrogen still needs to be introduced into the chamber to clean out excess metal source precursors, unadsorbed products, etc., to purify the chamber to wait for the start of the next growth cycle; the purification time is 10-30s. The key to the ALD process lies in the self-limiting reaction principle, that is, in each cycle, the precursor molecules can only react with the active sites on the surface; once these sites are completely occupied, subsequent precursor molecules cannot be adsorbed or participate in the reaction; thereby ensuring that only one layer of atoms or molecules is added in each round of deposition, thereby achieving precise control of the thickness of the gate dielectric layer and making the prepared gate dielectric layer have extremely high uniformity.

[0020] S4, repeating steps S2 and S3 for many times, forming a primary gate dielectric layer of target thickness, i.e., a metal oxide layer, on the surface of the low-dimensional material. The target thickness of the primary gate dielectric layer is 1.5-2.5nm. Under low temperature conditions, hydrogen peroxide is easily physically adsorbed on the surface of the material and forms a primary seed layer on the surface of the material, which not only makes up for the defect that there are no dangling bonds on the surface of the low-dimensional material, but also ensures that a dense and uniform primary gate dielectric layer is prepared on the surface of the low-dimensional material; at the same time, in the process of preparing the primary dielectric layer, due to the moderate oxidizing property of hydrogen peroxide, the reaction with the metal source is more sufficient, which can effectively reduce the oxygen vacancies in each monolayer of the primary gate dielectric layer, reduce the surface state density of the primary gate dielectric layer, and at the same time will not destroy the structure of the low-dimensional material surface itself due to excessive oxidizing property. In addition, the formed primary dielectric layer can be used as a protective layer to prevent the structure of the low-dimensional material from being destroyed by ozone and high temperature. Therefore, on the basis of the primary dielectric layer, ozone with stronger oxidizing property can be used as an oxygen source to continue to grow the gate dielectric layer to the target thickness at high temperature.

[0021] In the process of preparing the primary gate dielectric layer of target thickness, different metal source precursors are used, and the corresponding deposition cycle and deposition process parameters will also be different. For example, when the primary gate dielectric layer is aluminum oxide (Al 2 O 3 ), trimethylaluminum is preferred as the metal source precursor, the temperature in the metal source bottle needs to be heated to 20-40°C, the temperature outside the chamber is 80-150°C, the temperature inside the chamber is 50-120°C, and the growth cycle is 50-150 cycles; when the primary gate dielectric layer is hafnium oxide (HfO 2 ), the metal source precursor is preferably tetrakis(dimethylamino)hafnium or tetrakis(ethylmethylamino)hafnium, the temperature in the metal source bottle needs to be heated to 50-80°C, the temperature outside the chamber is 80-150°C, the temperature inside the chamber is 50-120°C, and the growth cycle is 50-140 cycles; when the primary gate dielectric layer is yttrium oxide (Y 2 O 3), the metal source precursor preferably uses yttrium tri(methylcyclopentadienyl)oxide, the temperature in the metal source bottle needs to be heated to a range of 180-200°C, the temperature outside the chamber is 150-250°C, the temperature inside the chamber is 120-200°C, and the growth cycle is 50-160 cycles; the specific number of growth cycles can be set according to the target thickness requirements. In addition, the primary gate dielectric layer of the target thickness is composed of a plurality of single layers stacked together, and the multiple single layers in the primary gate dielectric layer can be the same metal oxide layer obtained by reacting the same metal source precursor with a hydrogen peroxide precursor, or different types of metal oxide layers obtained by reacting different metal source precursors with a hydrogen peroxide precursor; at the same time, when preparing each single layer in the primary gate dielectric layer, the metal source precursor used is different, and the corresponding deposition process parameters are also different.

[0022] S5. In the instrument setting interface, switch the oxygen source from hydrogen peroxide to ozone, and introduce ozone precursor (O 3 ), so that the ozone precursor is adsorbed on the primary gate dielectric layer on the surface of the low-dimensional material, and then high-purity nitrogen is introduced into the chamber to purify the chamber. The pulse duration of the ozone precursor is 20-500ms. The purpose of using high-purity nitrogen to purify the chamber is to blow away the excess and unadsorbed ozone precursor; the purification time is controlled within the range of 10-30s.

[0023] S6. Raise the temperature in the chamber to 230-320°C, and at the same time raise the temperature in the metal source bottle to the rated temperature, so that metal source vapor is formed in the metal source bottle and brought into the chamber by high-purity nitrogen through a pipeline; allow the metal source precursor to react with the ozone precursor adsorbed on the primary gate dielectric layer, and then introduce high-purity nitrogen into the chamber to purify the chamber; complete a reaction cycle.

[0024] S7, repeating steps S5 and S6 for many times, forming a gate dielectric layer of target thickness on the surface of the low-dimensional material. Steps S5, S6 and S7 are to use an ozone precursor as an oxygen source, and react with a metal source under high temperature conditions to achieve the effect of continuing to grow a single layer of the gate dielectric layer on the primary gate dielectric layer and preparing a gate dielectric layer of target thickness; for example, when the gate dielectric layer that continues to grow on the primary gate dielectric layer is aluminum oxide or hafnium oxide, the temperature in the chamber needs to be raised to 250°C during the reaction of the metal source precursor and the ozone precursor; when the gate dielectric layer that continues to grow on the primary gate dielectric layer is yttrium oxide, the temperature in the chamber needs to be raised to 300°C during the reaction of the metal source precursor and the ozone precursor; compared with the above-mentioned preparation of the primary gate dielectric layer using a hydrogen peroxide precursor as an oxygen source, the temperature set in the chamber is significantly increased during the reaction process of continuing to grow the gate dielectric layer on the primary gate dielectric layer. The target thickness of the gate dielectric layer needs to be set according to actual usage requirements. The target thickness of the gate dielectric layer is generally 5-12 nm. If a thicker or thinner gate dielectric layer is required, this can be achieved by appropriately adjusting the growth cycle. Example 1

[0025] S1. Place the substrate with carbon nanotubes in the chamber of an ALD reaction device, and adjust the pressure inside the chamber to 10 Pa.

[0026] S2. A hydrogen peroxide precursor is introduced into the chamber for primary surface adsorption, so that the hydrogen peroxide is adsorbed on the surface of the carbon nanotubes; the carrier gas volume of the hydrogen peroxide precursor is controlled to be 20 sccm, and the pulse duration is 300 ms. After that, high-purity nitrogen is introduced into the chamber to purify the chamber for 20 s.

[0027] S3, raising the temperature in the chamber to 80°C, and at the same time, using tetrakis(dimethylamino)hafnium as a metal source precursor, and raising the temperature in the metal source bottle containing tetrakis(dimethylamino)hafnium to 60°C, and then bringing the tetrakis(dimethylamino)hafnium vapor formed in the metal source bottle into the chamber through a pipeline by high-purity nitrogen; controlling the carrier gas volume of the tetrakis(dimethylamino)hafnium precursor to 20sccm, and the pulse time of the tetrakis(dimethylamino)hafnium precursor to 300ms; allowing the tetrakis(dimethylamino)hafnium precursor to react with the hydrogen peroxide precursor adsorbed on the surface of the carbon nanotubes to form a single layer of the primary gate dielectric layer on the surface of the carbon nanotubes, i.e., a hafnium oxide layer; after the reaction is completed, introducing high-purity nitrogen into the chamber to purify the chamber for 30s.

[0028] S4, repeating steps S2 and S3 multiple times to form a primary gate dielectric layer (HfO) with a thickness of 2 nm on the surface of the carbon nanotubes. 2 ).

[0029] S5. In the instrument setting interface, switch the oxygen source from the hydrogen peroxide source to the ozone source, and introduce an ozone precursor into the chamber so that the ozone precursor is adsorbed on the primary gate dielectric layer on the surface of the carbon nanotubes. Control the carrier gas volume of the ozone precursor to 20 sccm and the pulse duration to 400 ms. Then, introduce high-purity nitrogen into the chamber to purify the chamber for 30 s.

[0030] S6. Raise the temperature in the chamber to 250°C. At the same time, use tetrakis(dimethylamino)hafnium as a metal source precursor, and raise the temperature in the metal source bottle containing tetrakis(dimethylamino)hafnium to 60°C. Then, introduce the tetrakis(dimethylamino)hafnium precursor carried by high-purity nitrogen into the chamber; control the carrier gas volume of the tetrakis(dimethylamino)hafnium precursor to 20sccm, and the pulse time to 300ms; allow the tetrakis(dimethylamino)hafnium precursor to react with the ozone precursor adsorbed on the surface of the primary gate dielectric layer to form a single layer on the primary gate dielectric layer, i.e., a hafnium oxide layer; after the reaction is completed, introduce high-purity nitrogen into the chamber to purify the chamber for 30s.

[0031] S7, repeating steps S5 and S6 multiple times to form a gate dielectric layer (HfO) with a thickness of 5 nm on the surface of the carbon nanotubes. 2 ).like Figure 1 As shown in the figure, the dark part in the figure is the prepared gate dielectric layer, and the carbon nanotubes are below the dark part. It can be seen from the figure that the gate dielectric layer formed on the surface of the carbon nanotubes has good density and uniformity. Afterwards, the carbon nanotubes with the gate dielectric layer are made into FET devices, and the performance of the FET devices is tested.

[0032] From the transfer characteristic curve of FET device, we can know that Figure 2 As shown, the on-state current of the FET device is about 140μA; and the size of its hysteresis can be calculated based on (-0.53005, -2.05E -5 ) and (-0.25999, -2.08E -5 ) is calculated by the difference between them.

[0033] Comparative Example 1 S1. Place the substrate with carbon nanotubes in the chamber of an ALD reaction device, and adjust the pressure inside the chamber to 10 Pa.

[0034] S2. Use water as the oxygen source and introduce a water vapor precursor into the chamber for primary surface adsorption, so that the water vapor precursor is adsorbed on the surface of the carbon nanotubes; control the carrier gas volume of the water vapor precursor to 20 sccm and the pulse duration to 300 ms. Then, introduce high-purity nitrogen into the chamber to purify the chamber for 20 s.

[0035] S3, raising the temperature in the chamber to 250°C, and at the same time, using tetrakis(dimethylamino)hafnium as a metal source, and raising the temperature in the metal source bottle containing tetrakis(dimethylamino)hafnium to 60°C, then introducing a tetrakis(dimethylamino)hafnium precursor carried by high-purity nitrogen into the chamber; controlling the carrier gas volume of the tetrakis(dimethylamino)hafnium precursor to 20sccm, and the pulse time to 300ms; allowing the tetrakis(dimethylamino)hafnium precursor to react with the water vapor precursor adsorbed on the surface of the carbon nanotubes to form a single layer of the gate dielectric layer, and after the reaction is completed, introducing high-purity nitrogen into the chamber to purify the chamber for 30s.

[0036] S4, repeating steps S2 and S3 multiple times to form a gate dielectric layer (HfO) with a thickness of 5 nm on the surface of the carbon nanotubes. 2 ).like Figure 2 As shown in the figure, it can be seen that there are pinhole-like vacancies on the gate dielectric layer formed on the surface of the carbon nanotube, as indicated by the arrow; that is, the gate dielectric layer formed on the surface of the carbon nanotube is not dense enough and does not completely cover the bottom carbon nanotube; further indicating that the gate dielectric layer prepared using water as an oxygen source will have defects, and its density and uniformity are poor. Afterwards, the carbon nanotube with the gate dielectric layer is made into a FET device, and the performance of the FET device is tested.

[0037] From the transfer characteristic curve of FET device, we can know that Figure 2 As shown, the on-state current of the FET device is about 50μA; and the size of its hysteresis is based on (-1. 35004, -1.96E -5 ) and (-0.84005, -1.97E -5 ) is calculated by the difference between them.

[0038] Comparing the gate dielectric layer prepared in Example 1 with the gate dielectric layer prepared in Comparative Example 1, it can be seen that the gate dielectric layer prepared in Example 1 has better compactness and uniformity. Comparing the performance of the FET device prepared in Example 1 with the performance of the FET device prepared in Comparative Example 1, it can be seen that the on-state current of the FET device prepared in Comparative Example 1 is significantly smaller than the on-state current of the FET device prepared in Example 1, and the FET device prepared in Comparative Example 1 has a larger hysteresis; thus, it can be seen that compared with the FET device prepared in Comparative Example 1, the performance of the FET device prepared in Example 1 is better. It is further explained that when the semiconductor material is the same and the thickness of the gate dielectric layer is also the same, the gate dielectric layer formed on the surface of the low-dimensional material with hydrogen peroxide-ozone as the oxygen source can not only meet the requirements of the field effect transistor for a high-quality gate dielectric layer; it can also avoid the occurrence of a large number of defects and vacancies on the gate dielectric layer due to insufficient reaction between the oxygen source and the metal source, resulting in poor performance problems such as small on-state current and large hysteresis of the corresponding FET device. In addition, since hydrogen peroxide has moderate oxidizing properties, hydrogen peroxide is first used as an oxygen source to grow a primary dielectric layer with low interface state density under low temperature conditions; then ozone is used as an oxygen source to continue growing at high temperature to prepare a gate dielectric layer of target thickness; this gate dielectric layer growth method not only does not destroy the structure of the material itself, but also can ensure the density and uniformity of the primary dielectric layer in contact with the low-dimensional material; at the same time, it has all the advantages of gate dielectrics prepared under high temperature and high oxidation conditions.

[0039] The gate dielectric layer prepared by the preparation process provided by the present invention can meet the quality requirements of the field effect transistor for a high-quality gate dielectric layer; however, it does not rule out the possibility that a gate dielectric layer of a target thickness directly grown under low temperature conditions using hydrogen peroxide with moderate oxidizing properties as an oxygen source can also meet the quality requirements of the field effect transistor for a high-quality gate dielectric layer.

[0040] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the scope of protection of the present invention. For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is limited by the attached claims rather than the above description, and it is intended to include all changes within the meaning and scope of the equivalent elements of the claims in the present invention.

Claims

1. A process for preparing a gate dielectric layer on the surface of a low-dimensional material field effect transistor, characterized in that: The steps include: S1, placing a substrate having a low-dimensional material in the chamber of the ALD reaction device, and adjusting the pressure inside the chamber to 5-50Pa; S2, introducing a hydrogen peroxide precursor into the chamber for surface adsorption, so that the hydrogen peroxide precursor is adsorbed on the surface of the low-dimensional material, and then introducing high-purity nitrogen into the chamber to purify the chamber; S3, raising the temperature in the chamber from room temperature to 50-200°C, and at the same time raising the temperature in the metal source bottle to the rated temperature, so that metal source vapor is formed in the metal source bottle, and is brought into the chamber through a pipeline by high-purity nitrogen gas, so that the metal source precursor reacts with the hydrogen peroxide precursor adsorbed on the surface of the low-dimensional material to form a single layer of the primary gate dielectric layer, and then, high-purity nitrogen gas is introduced into the chamber to purify the chamber, completing a growth cycle; S4, repeating steps S2 and S3 multiple times to form a primary gate dielectric layer of target thickness on the surface of the low-dimensional material; S5, introducing an ozone precursor into the chamber to allow the ozone precursor to be adsorbed on the primary gate dielectric layer on the surface of the low-dimensional material, and then introducing high-purity nitrogen into the chamber to purify the chamber; S6, raising the temperature in the chamber to 230-320°C, and at the same time raising the temperature in the metal source bottle to the rated temperature, so that metal source vapor is formed in the metal source bottle, and is brought into the chamber through a pipeline by high-purity nitrogen gas, so that the metal source precursor reacts with the ozone precursor adsorbed on the primary gate dielectric layer, and then high-purity nitrogen gas is introduced into the chamber to purify the chamber, completing a growth cycle; S7. Repeat steps S5 and S6 multiple times to form a gate dielectric layer of target thickness on the surface of the low-dimensional material.

2. The process for preparing a surface gate dielectric layer of a low-dimensional material field effect transistor according to claim 1, characterized in that: In the step S2, the carrier gas volume of the hydrogen peroxide precursor is 18-25 sccm, and the pulse duration of the hydrogen peroxide precursor is 20-500 ms.

3. The process for preparing a surface gate dielectric layer of a low-dimensional material field effect transistor according to claim 2, characterized in that: In step S3, the rated temperature is 20-200°C; The carrier gas volume of the metal source precursor is 20 sccm, and the pulse duration of the metal source precursor is 20-500 ms.

4. The process for preparing a surface gate dielectric layer of a low-dimensional material field effect transistor according to claim 2, characterized in that: In the step S3, the metal source precursor is any one of trimethylaluminum, tetrakis(dimethylamino)hafnium, tetrakis(ethylmethylamino)hafnium, and tri(methylcyclopentadienyl)yttrium.

5. The process for preparing a surface gate dielectric layer of a low-dimensional material field effect transistor according to claim 1, characterized in that: The growth cycle of the primary gate dielectric layer is 10-200 cycles; the target thickness of the primary gate dielectric layer is 1.5-2.5 nm.

6. The process for preparing a surface gate dielectric layer of a low-dimensional material field effect transistor according to claim 1, characterized in that: The chamber is purified for 10-30 seconds.

7. The process for preparing a surface gate dielectric layer of a low-dimensional material field effect transistor according to claim 1, characterized in that: The target thickness of the gate dielectric layer is 5-12 nm.

Citation Information

Patent Citations

  • Method for realizing enhanced gallium nitride transistor with low on-resistance

    CN110676172A

  • Manganese dioxide nano-composite film material and preparation method thereof

    CN111748794A

  • Atomic layer deposition of Hf3N4 / HfO2 films as gate dielectrics

    US20060189154A1

  • Methods of atomic layer deposition of hafnium oxide as gate dielectrics

    US20130316546A1